Anthropometric Parameters among Children Under 6 Years with Stunting - Abdul Malik Setiawan; Apriyani Puji Hastuti (Journal of Ners and Midwifery, 2021)
Anthropometric measurement is a quantitative measurement as a nutritional status and can describe composition of the body. Stunting is when children have a low height-for-age. There are potential causes of stunting in Indonesia, including factor maternal nutritional status, breastfeeding practice, complementary feeding practice, exposure to infection, and related distal determinants such as education, dietary pattern, health care, and water sanitation hygiene. The objective of the research was to assess the association between gender, age and anthropometric parameters (weight-for-age, weight-for-height, body mass index for age) among children-under-six-years with stunting.Â  The research used a cross sectional method which used documentation research of gender, weight, height or length and age reports of 25.158 children under six years. The anthropometric parameters of the children were categorized using weight-for-age (WAZ), weight-for-height (WHZ), body mass index for age. This research used spearman rank test and binary logistic regression to analyze association between gender, age, weight-for-age, weight-for-height, body mass index for age, and height or length-for-age. Results: There were male 14.027 (55.8%), 2-6 years 15.789 (62.8%), with normal anthropometric parameter (weight- for-age, weight-for-height, and body mass index for age in stunted children. There was no significantly correlation between the children's gender and height-for-age (ï¡=0.096) and OR 0.993 (0.933- 1.056). Furthermore, there was low significantly correlation between age, anthropometric parameter (weight-for-age WAZ, weight-for-height WHZ and body mass index for age) with height-for-age (ï¡=0.000). Stunted children who had normal nutritional status were 0.469 times more likely to experience stunting.